2020
DOI: 10.3389/fpls.2019.01635
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Changes in the Apoplast Accompany Leaf Senescence in Arabidopsis

Abstract: The apoplast, i.e. the cellular compartment external to the plasma membrane, undergoes important changes during senescence. Apoplastic fluid volume increases quite significantly in senescing leaves, thereby diluting its contents. Its pH elevates by about 0.8 units, similar to the apoplast alkalization in response to abiotic stresses. The levels of 159 proteins decrease, whereas 24 proteins increase in relative abundance in the apoplast of senescing leaves. Around half of the apoplastic proteins of non-senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 149 publications
(179 reference statements)
1
18
0
Order By: Relevance
“…Cellular co-silencing of LIN6 and LIN8 CWIs in tomatoes reduced the induction of pathogenesis-related (PR) genes together with pathogenesis symptom development ( Kocal et al, 2008 ), suggesting a direct relationship between the increase in cell wall invertase expression and the increase in SlPR1 and SlACS2 expression. Cell wall invertases were also shown to play a role in delaying senescence and drought tolerance ( Albacete et al, 2015 ), while PR-proteins have been shown to be involved in processes like SA-induced senescence and leaf abscission as well ( Espinoza et al, 2007 ; Kim et al, 2015 ; Borniego et al, 2020 ), suggesting that these genes may be involved in crosstalk between abiotic stress response and disease symptom development. The high induction of dehydrin SlTAS14 in MM and NIL- Ol-1 , observed in concord with the pathogenesis and ethylene response under combined stress is likely an indication of the ABA-dependent stress pathway being induced under drought and further enhanced under combined stress, and may also be indicative of increased ROS and ROS scavenging activity ( Halder et al, 2018 ), which is also supported by the high expression levels of SlAPX1 under these conditions ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular co-silencing of LIN6 and LIN8 CWIs in tomatoes reduced the induction of pathogenesis-related (PR) genes together with pathogenesis symptom development ( Kocal et al, 2008 ), suggesting a direct relationship between the increase in cell wall invertase expression and the increase in SlPR1 and SlACS2 expression. Cell wall invertases were also shown to play a role in delaying senescence and drought tolerance ( Albacete et al, 2015 ), while PR-proteins have been shown to be involved in processes like SA-induced senescence and leaf abscission as well ( Espinoza et al, 2007 ; Kim et al, 2015 ; Borniego et al, 2020 ), suggesting that these genes may be involved in crosstalk between abiotic stress response and disease symptom development. The high induction of dehydrin SlTAS14 in MM and NIL- Ol-1 , observed in concord with the pathogenesis and ethylene response under combined stress is likely an indication of the ABA-dependent stress pathway being induced under drought and further enhanced under combined stress, and may also be indicative of increased ROS and ROS scavenging activity ( Halder et al, 2018 ), which is also supported by the high expression levels of SlAPX1 under these conditions ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of cohorts of genes induced during senescence revealed that the activation of cell wall degradation and modification (cellulose, hemicellulose and pectin) followed the decline of cell biogenesis pathways, as found in other species [11,13,49,50]. Moreover, some genes related to cell wall modification such as expansins were specifically induced during dark treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Accumulation of PR proteins was also observed in the intercellular spaces of barley leaves during natural senescence ( Tamás et al., 1998 ). Protein profiling of apoplastic proteins of naturally, but not dark-induced, senescing leaves of Arabidopsis revealed that the most abundant SAG proteins were PR2 and PR5 ( Borniego et al., 2020 ). Pathogens interfere with the host development by modifying the signalling pathways and regulating progression of plant senescence to meet their nutritional demands, whereas plants counteract by inducing a hypersensitive response to kill its own cells.…”
Section: Discussionmentioning
confidence: 99%